Precarity and dehumanisation in higher education. Issue 1 (1st March 2021) - Mason, Olivia; Megoran, Nick
Abstract: The increased reliance of universities on a pool of highly skilled but poorly paid casualised academic labour for teaching and research has emerged as a defining feature of higher education provision under neoliberal New Public Management. Based on seventeen visual timeline interviews with academics in the North East of England, this article augments and extends existing studies of precarity through a framing of dehumanisation and humanisation. Specifically, we suggest that casualisation is dehumanising in four ways: it renders individuals invisible; it leaves them vulnerable to exploitation; it denies them academic freedom; and it hampers them in constructing a life narrative projecting into the future. We conclude that casualisation is not simply the product of a reprehensible political economy, but that it is an afront to the very meaning and dignity of being human.